The novel expression of clonality following whole-genome multiplication compensates for reduced fertility in natural autopolyploids - Šingliarová, Barbora; Hojsgaard, Diego; Müller-Schärer, Heinz; Mráz, Patrik (Proceedings. Biological sciences, 2023)
Exploring the fitness consequences of whole-genome multiplication (WGM) is essential for understanding the establishment of autopolyploids in diploid parental populations, but suitable model systems are rare. We examined the impact of WGM on reproductive traits in three major cytotypes (2x, 3x, 4x) of Pilosella rhodopea, a species with recurrent formation of neo-autopolyploids in mixed-ploidy populations. We found that diploids had normal female sporogenesis and gametogenesis, high fertility, and produced predominantly euploid seed progeny. By contrast, autopolyploids had highly disturbed developmental programs that resulted in significantly lower seed set and a high frequency of aneuploid progeny. All cytotypes, but particularly triploids, produced gametes of varying ploidy, including unreduced ones, that participated in frequent intercytotype mating. Noteworthy, the reduced investment in sexual reproduction in autopolyploids was compensated by increased production of axillary rosettes and the novel expression of two clonal traits: adventitious rosettes on roots (root-sprouting), and aposporous initial cells in ovules which, however, do not result in functional apomixis. The combination of increased vegetative clonal growth in autopolyploids and frequent intercytotype mating are key mechanisms involved in the formation and maintenance of the largest diploid-autopolyploid primary contact zone ever recorded in angiosperms.
Keywords: mixed-ploidy; apospory; unreduced gametes; Ploidies; Reproduction; fertilita; Seeds; clonality; ploidie; rozmnožování; aneuploidy; polyploidie; Polyploidy; root-sprouting; Fertility; Diploidy; semena rostlinná; diploidie